Understanding Acid Lability of Cysteine Protecting Groups - Ramos-Tomillero, Iván (Molecules, 2013)
Cys-disulfide bonds contribute to the stabilization of peptide and protein structures. The synthesis of these molecules requires a proper protection of Cys residues, which is crucial to prevent side-reactions and also to achieve the correct Cys connectivity. Here we undertook a mechanistic study of a set of well-known acid-labile Cys protecting groups, as well other new promising groups, in order to better understand the nature of their acid-lability. The stability of the carbocation generated during the acid treatment was found to have a direct impact on the removal of the protective groups from the corresponding protected Cys-containing peptides. Hence a combination of steric and conjugative effects determines the stability of the carbocations generated. Here we propose diphenylmethyl (Dpm) as a promising protecting group on the basis of its intermediate relative carbocation stability. All the optimized geometries and energies presented in this study were determined using a B3LYP/6-31G(d,p) calculation. The results discussed herein may be of broader applicability for the development of new protecting groups.